"Everything Happens for a Reason": Children's Beliefs About Purpose in Life Events. Issue 2 (18th October 2014) - Banerjee, Konika; Bloom, Paul
Abstract : Do children believe that "everything happens for a reason?" That is, do children endorse purpose‐based, teleological explanations for significant life events, as they do for social behavior, artifacts, biological properties, and natural kinds? Across three experiments, 5‐ to 7‐year‐olds ( N  =   80), 8‐ to 10‐year‐olds ( N  =   72), and adults ( N  =   91) chose between teleological and nonteleological accounts of significant life events and judged how helpful those accounts were for understanding an event's cause. Five‐ to 7‐year‐olds favored teleological explanations, but this preference diminished with age. Five‐ to 7‐year‐olds and 8‐ to 10‐year‐olds also found teleological explanations more helpful than did adults. Perceiving purpose in life events may therefore have roots in childhood, potentially reflecting a more general sensitivity to purpose in the social and natural worlds.